2018
DOI: 10.18502/kls.v4i4.2270
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge about Risk Factors for Cancer among Adults in Nepal

Abstract: Cancer accounts for 8% mortality in Nepal and is an emerging public health concern.It is believed that increasing the basic knowledge about cancer is vital to decreasing the burden of cancer diagnosis and treatment. The purpose of this study was to identify cancer awareness among Nepali adults. A descriptive, cross-sectional study was conducted in five wards of Lalitpur Sub-metropolitan city. A random sample of 300 Nepali adults aged 20-60 years participated in this study. Most participants (45.3%) were aged 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 8 publications
0
9
0
1
Order By: Relevance
“…Cervical cancer is an important issue in Nepal; hence, proper strategies should be developed to increase women’s participation in screening programs [41]. Lack of proper information and less perceived seriousness were barriers hindering cervical cancer screening among mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical cancer is an important issue in Nepal; hence, proper strategies should be developed to increase women’s participation in screening programs [41]. Lack of proper information and less perceived seriousness were barriers hindering cervical cancer screening among mothers.…”
Section: Discussionmentioning
confidence: 99%
“…The 2018 report by the World Health Organization (WHO) indicated that lung cancer was responsible for nearly one in five (18.4%) cancer-related deaths across the globe [1]. Increasing cancer-related mortality in low-and middle-income countries (LMICs), including sub-Saharan Africa (SSA), are attributable to aging and pervasive risk factors, including cigarette smoking, alcohol use, unhealthy diet and lack of physical activity [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…These numbers are expected to double in the next 20 years due to the aging and population growth, as well as the changes in lifestyle factors. These lifestyle factors are associated with urbanization and economic development of risk factors, such as smoking, obesity, physical inactivity and dietary patterns (4,9,10). It is believed that increasing the awareness about lung cancer is key to reducing the diagnosis and treatment delays (10).…”
Section: Introductionmentioning
confidence: 99%
“…These lifestyle factors are associated with urbanization and economic development of risk factors, such as smoking, obesity, physical inactivity and dietary patterns (4,9,10). It is believed that increasing the awareness about lung cancer is key to reducing the diagnosis and treatment delays (10). Evidence suggests that a significant portion of the increase in cancer is due to several factors, including poor awareness of the signs, symptoms, and risk factors for cancer; poor availability of tests or screening programs; and limited access to standard treatment (5,10,11).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation